Development of the Ni-Kshay Portal as An Integrated Digital System for Effective Tuberculosis (TB) Management in Indonesia - Khusnul Khotimah Arum Nurcahyanti; Oksita Asri Widyayanti; Ilham Rahmansyah (Indonesian Journal of Global Health Research, 2026)
Tuberculosis (TB) remains a major public health burden in Indonesia, with reported cases increasing from 724,309 in 2022 to approximately 889,000 by early 2025. The current Tuberculosis Information System (SITB) has not fully supported rapid and accurate reporting due to delays, duplicated records, limited interoperability with other health information systems, and insufficient data quality controls. In contrast, India has successfully improved TB management efficiency through the Ni-kshay Portal, an integrated digital platform that enhances case notification and service coordination. This study aimed to conduct a needs analysis as the foundational step in developing and adapting the Ni-kshay Portal for implementation in Indonesia to ensure that the system is relevant, efficient, and aligned with national TB elimination goals. A qualitative approach was applied using the Waterfall system development model and the PIECES framework. The study involved 24 participants, consisting of 20 users and persons in charge of the Tuberculosis Information System (SITB) from primary health centers and 4 respondents from referral hospitals who were directly engaged in the implementation and operational use of the system. Data were collected through in-depth interviews, field observations, document reviews, and stakeholder validation sessions. A total of 20 primary health centers, four referral hospitals, and the Banyumas District Health Office participated in identifying functional and non-functional system requirements. Results revealed significant challenges in the current reporting system, including 2–4-week delays, server overload, duplicate patient records, weak SITB–SIMRS–BPJS synchronization, and high manual data-entry workload. The PIECES analysis identified essential requirements for the upgraded system, including real-time reporting, automated national ID (NIK) validation, cross-system API integration, centralized dashboards, streamlined digital workflows, activity logs, automated reminders, and digital referral-back features. The study concludes that an integrated digital TB reporting platform is urgently needed to improve timeliness, data quality, and case monitoring. Subsequent research stages will focus on prototype development and field testing to assess technical feasibility and potential system impact.